Staring into the eye of the Medusa - Lindroos, Lukas (My University, 2011)
The Medusa is a nearby merger galaxy. The galaxy harbours an ongoing starburst with very efficient conversion of hydrogen to stars. This seems to happen despite the lack of high density gas. In this project I have studied the dynamics and structure of the molecular gas by looking at the rotational CO 2-1 line. I used data recorded with the SMA interferometer. The data from SMA has allowed me to push the resolution to approximately 0"4 and generate the highest resolution molecular gas map of the Medusa yet. At this scale we have been able to observe giant molecular associations(GMAs). We find that the GMAs in general have larger velocity dispersion than what we would expect from their size. I will briefly discuss possible causes for this. In the high resolution data we also find the Eye of the Medusa: a hole in the CO emission that is also associated with radio continuum emission and H0. This seems to be the site of a dramatic star-forming event. The Eye of the Medusa is not located at the dynamical centre of the galaxy, but a few hundred parcecs out. Possibly where the inflowing gas meets the central rotation. The new data has also allowed us a good look at the dynamics of the molecular gas. We found a quickly rotating central body with evidence of inflowing gas moving on non-circular orbits. We propose that what we see might be a molecular ring. This dynamical structure could be helping the starburst by rapidly feeding new gas into the centre.
Keywords: Astronomi, astrofysik och kosmologi; Grundläggande vetenskaper; Stjärnors bildning och utveckling; Astronomy, Astrophysics and Cosmology; Basic Sciences; Formation and development of stars